Bacterial lysate for the prevention of chronic rhinosinusitis recurrence in children. Issue 6 (20th March 2017) - Chen, J; Zhou, Y; Nie, J; Wang, Y; Zhang, L; Shi, Q; Tan, H; Kong, W
Abstract: Background: Chronic rhinosinusitis is a common nasal disorder in children that is prone to recurrence. This study investigated the prevention of chronic rhinosinusitis recurrence with bacteria lysate in children. Methods: Bacteria lysate was administered 10 days per month for 3 months to children with chronic rhinosinusitis, who had just entered a remission phase. Visual analogue score, nasal symptoms scores, rhinitis attack frequency and antibiotic use were assessed at three months and one year. Results: At one year of follow up, the visual analogue score, nasal discharge and obstruction scores, number of days with rhinitis attacks per month and number of days with antibiotic use per month were significantly decreased in the prevention group versus the control group ( p < 0.05). Conclusion: Bacterial lysate used in the remission period of rhinosinusitis in children was shown to provide long-term prophylaxis. Bacterial lysate can effectively reduce the frequency of rhinosinusitis attacks and ameliorate attack symptoms.